Granulometric, Chemical, and Mineralogical Evaluation of Greek Lignite Bottom Ash for Potential Utilization in Concrete Manufacturing - Argyro Asvesta; Ioannis Kapageridis; Agapi Vasileiadou; Kyros Koios; Nikolaos Kantiranis (Materials Proceedings)
Coal bottom ash is used globally in various applications in the construction industry to reduce its negative environmental impacts. In this study, the potential utilization of lignite bottom ash from four power plants in Greece in concrete manufacturing was evaluated through granulometric, chemical, and mineralogical analyses. The particle-size distribution of bottom ash obtained from dry sieving resembles that of sand, making bottom ash suitable for replacing fine aggregates in the production of concrete. Its chemical composition, determined with selective point analyses energy dispersive spectroscopy (EDS), reveals high amounts of silica and alumina indicating pozzolanic properties, and high calcium contents suggesting hydraulic/cementitious character. Mineralogical characterization, obtained from powder X-Ray diffraction analyses (XRD), displays the prevalence of amorphous matter, calcite, quartz, aluminosilicate minerals, and portlandite, implying a beneficial pozzolanic and hydraulic activity in concrete manufacturing.